An Analytical Model for Aerostatic Thrust Bearings Based on the Average Pressure of the Area Surrounded by Orifice - Jian Zheng; Jianwei Wu; Huan Liu; Jiyao Wang; Pengyue Zhao (Lubricants)
Aerostatic thrust bearings are widely used in advanced equipment such as lithography machines due to their excellent lubrication performance. In this study, computational fluid dynamics (CFD) was employed for the analysis of errors in the calculation of static characteristics of bearings based on the pressure behind the orifice. We put forth an analytical model for calculating the static characteristics of bearings utilizing the average pressure (PdAVE) within the area surrounded by orifice. By analyzing the influence of various structural parameters, film thickness, and gas supply pressure on PdAVE in aerostatic bearings, we derived an approximate expression for the average pressure coefficient, which was subsequently verified through experiments. The findings demonstrate that the analytical model for aerostatic bearings, formulated using PdAVE, can accurately predict the static characteristics of the bearings. The working range corresponding to the optimal stiffness of the bearings is entirely consistent, and the prediction error of the bearing capacity within the optimal working range is less than 5%. This provides a more precise and effective performance prediction model for rectangular aerostatic thrust bearings in engineering design.